Trends in smartphone-based walking speed measurement and its association with frailty in community dwellers - KUBOTA, Anna; HASHIDA, Kohichi; MIYATA, Hiroaki; HOTTA, Kazuki; YAMASHITA, Masashi; KAMIYA, Kentaro (Japanese Journal of Geriatric Therapy, 2024)
Objective: Technological innovations, such as smartphones, have made it possible to measure walking speed in daily life; however, the accuracy of and trends in gait speed measurement in frail older adults still need to be thoroughly investigated. This study examined the accuracy of smartphone-measured walking speed and its relationship with frailty in older adults attending preventive care facilities. Methods: Eight subjects who had been attending preventive care facilities were included in this prospective study. A walking speed measurement app, Chami, was installed on their personal smartphones, which were used to obtain the daily number of steps and daily walking speed during the one-year follow-up period. The association between the smartphone-recorded walking speed and the level of frailty assessed by the revised Japanese version of the Cardiovascular Health Study criteria was examined using Spearman's rank correlation coefficient. Results: Three of the subjects in this study were frail, and five were prefrail. A tendency was observed in those with a greater degree of frailty to have slower walking speeds measured by the app (ρ = –0.2142), fewer days in which walking speeds could be recorded (ρ = –0.7433), and a greater coefficient of variation for recorded walking speed data(ρ = 0.4662). Conclusion: The degree of frailty may be related to the smartphone-based walking speed of older adults, as well as the accuracy of the measurement.